Toxicity differentiation of oat varieties in celiac disease - Gavriluk, Inna; Alpatieva, Natalia; Leontieva, Natalia; Krasilnikov, Valerii; Loskutov, Igor (MTT, 2004)
Celiac disease (CD) is a permanent intolerance to the grain s storage protein gluten : gliadins (wheat), secalins (rye), hordeins (rye) and possibly avenins (oats). The only possible treatment of the CD is the observation of a strict gluten free diet during lifetime. The toxic role of oats is controversial. Recently it was shown that ingestion of moderate amounts of oats does not have a harmful effect in adult patients with CD (Janatuinen at al. 2002) and was suggested that the immunogenetic sequences in gliadin are not present in avenin (Kilmartin at al. 2003). However, a specially grown and tested oat product was used in these studies. In our study we used ELISA method to compare 8 oat varieties of different origin and to determine whether they can be safely included in a gluten free diet. It was shown that: a) the proteins of oat varieties are different by the toxicity for celiac patients; b) for composition of individual gluten-free diets the toxicity of oat varieties must be determined; c) by our preliminary data the oat variety Argamak selected in the North West Agricultural Institute (Russia) is the best one for gluten-free diet of certain types of patients; d) the blood serum of celiac patients have to be characterized both by quantity of antigliadin antibodies and by their ability to react with different types of antigenic determinant of oat proteins; e) in order to determine types of each celiac patient antigluten antibodies it is promising to prepare the prolamine fraction kits. Janatuinen, E. 2002. Gut 50: 332-335; Kilmartin, C. 2003. Gut 52: 47-52.
Keywords: Ka; oat varieties; avenin; celiac disease; antibodies